2008
DOI: 10.1024/0300-9831.78.3.105
|View full text |Cite
|
Sign up to set email alerts
|

Serum Carotenoid Concentrations in Postmenopausal Women from the United States with and without Osteoporosis

Abstract: Antioxidant defenses may be compromised in osteoporotic women. Little is known about fruit and vegetable or carotenoid consumption among postmenopausal women. The primary carotenoids in human serum are alpha- and beta-carotene, lycopene, beta-cryptoxanthin, lutein, and zeaxanthin. This study investigated the interrelationships among serum carotenoid concentrations, fruit and vegetable intake, and osteoporosis in postmenopausal women (n = 59, 62.7 +/- 8.8 y). Bone density was assessed by dual energy x-ray absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 34 publications
3
59
0
1
Order By: Relevance
“…Several research investigations have shown an inverse relationship between plasma/serum lycopene concentrations and risk of some cancers [142][143][144][145][146][147][148]. Similar associations have been reported for markers of cardiovascular disease, osteoporosis, cognitive function, and body weight [149][150][151][152][153][154][155][156]. Moreover, relationships between dietary intakes of tomato products or tomato extract supplements have been observed in epidemiological studies and clinical trials examining markers of some cancers, cardiovascular disease, and ultraviolet light-induced skin erythema [157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172].…”
Section: Tomatosupporting
confidence: 52%
“…Several research investigations have shown an inverse relationship between plasma/serum lycopene concentrations and risk of some cancers [142][143][144][145][146][147][148]. Similar associations have been reported for markers of cardiovascular disease, osteoporosis, cognitive function, and body weight [149][150][151][152][153][154][155][156]. Moreover, relationships between dietary intakes of tomato products or tomato extract supplements have been observed in epidemiological studies and clinical trials examining markers of some cancers, cardiovascular disease, and ultraviolet light-induced skin erythema [157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172].…”
Section: Tomatosupporting
confidence: 52%
“…Park et al [20] reported that carotene consumption was associated with reduced risk of OP after adjusting for age, BMI, hormone replacement therapy, and total caloric intake. Recent studies have also confirmed that carotenoid or carotene plays an important role in preventing bone loss [20][21][22]. Carotene's direct effect on bone health is largely derived from its antioxidant attributes [21].…”
Section: Discussionmentioning
confidence: 90%
“…Carotene's direct effect on bone health is largely derived from its antioxidant attributes [21]. Yang et al [22] suggested that lycopene and β-carotene, the primary forms of carotene in our body or diet contribute to the prevention of osteoporosis. This is because antioxidants can donate electrons to free radicals, leading to the elimination of oxidative stress [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis is considered the result of an imbalance in bone remodeling by inadequate osteoblasts activity and / or excessive osteoclasts activity, the cells responsible for bone resorption [30]. Calcitriol and PTH are closely related hormones in the context of bone physiology and pathophysiology, in calcium homeostasis and in bone mineralization.…”
Section: Discussionmentioning
confidence: 99%